FACTORS AFFECTING EFFICIENCY IN TENDERING PROCESS IN THE ENERGY SECTOR IN KENYA. - Kinyamasyo, Simon Mwanza; Kihara, Dr. Allan (International Journal of Supply Chain Management, 2019)
Purpose: The purpose of the study was to determine the factors that affect efficiency in tendering process in the energy sector with an aim of making recommendations. Methodology: The study employed a descriptive research design. The study preferred this method because it allowed an in-depth study of the subject. Data was collected using self-administered questionnaires. The study employed stratified random sampling technique in coming up with a sample size of 154 respondents from a total of 253 target population in the energy sector in Kenya. Pilot study was carried out to establish the validity and reliability of the research instruments. The instruments were designed appropriately according to the study objectives. The data collected was analyzed by use of descriptive and inferential statistics. The study used multiple regression and correlation analysis to show the relationship between the dependent variable and the independent variables. The data generated was keyed in and analyzed by use of Statistical Package of Social Sciences (SPSS) version 24 to generate information which was presented using charts, frequencies and percentages. Results: The results of regression analysis revealed that there was a significant positive relationship between dependent variable and independent variable at (Î² = 0.634), p=0.000 <0.05). The findings of the study indicated that information technology integration, regulatory framework, records management and supplier relationship management have a positive relationship with efficiency in tendering process in public procurement project. Unique Contribution to Policy and Practice: The study recommended that companies in the energy sector should embrace efficiency in tendering process and further researches should to be carried out in other institutions to find out if the same results can be obtained.